2013
DOI: 10.3390/ijms141019971
|View full text |Cite
|
Sign up to set email alerts
|

Eleven Novel Polymorphic Microsatellite Loci for Oval Squid Sepioteuthis Lessoniana (Shiro-Ika Type)

Abstract: The oval squid Sepioteuthis lessoniana is one of the most economically important squid species in Japan; however, its population structure is poorly understood due to the lack of hypervariable markers. Such information is critical for managing sustainable fisheries, as well as for ensuring the existence of wild S. lessoniana stocks. Eleven candidate microsatellite loci were isolated from a small insert genomic DNA library. Polymorphisms in these 11 loci were screened in 24 wild individuals. The number of allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Using the SSR technique, Tomano et al (2013) showed that the heterozygosity of the population in Mugi (Japan) was 0.697 and Zheng et al (2012) indicated the expected heterozygosity of the population in Hainan island was 0.852. Comparing to the results of these studies, the genetic diversity levels of the Con Dao and Phu Quoc populations based on SCoT and CBDP data sets were relatively low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the SSR technique, Tomano et al (2013) showed that the heterozygosity of the population in Mugi (Japan) was 0.697 and Zheng et al (2012) indicated the expected heterozygosity of the population in Hainan island was 0.852. Comparing to the results of these studies, the genetic diversity levels of the Con Dao and Phu Quoc populations based on SCoT and CBDP data sets were relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate that CBDP markers can be applied in population genetic studies in animals, in the present study, two DNA fingerprinting data sets of S. lessoniana populations generated by CBDP and SCoT techniques were compared together. For S. lessoniana species, previous studies on population genetic diversity were conducted by two groups of methods, including using mitochondrial DNA sequence data (Aoki et al, 2008;Cheng et al, 2013) and using DNA fingerprinting data generated via the Allozyme marker (Pratoomchat et al, 2001), Microsatellite marker (Tomano et al, 2013;Zheng et al, 2012). To demonstrate that CBDP markers can be applied in population genetic studies in animals, in the present study, two DNA fingerprinting data sets of S. lessoniana populations generated by CBDP and SCoT techniques are compared together.…”
Section: Introductionmentioning
confidence: 99%